Women and human development : the capabilities approach - Nussbaum, Martha Craven, 1947- (John Robert Seeley lectures. ;, 2000)
In this major book Martha Nussbaum, one of the most innovative and influential philosophical voices of our time, proposes a kind of feminism that is genuinely international, argues for an ethical underpinning to all thought about development planning and public policy, and dramatically moves beyond the abstractions of economists and philosophers to embed thought about justice in the concrete reality of the struggles of poor women. Nussbaum argues that international political and economic thought must be sensitive to gender difference as a problem of justice, and that feminist thought must begin to focus on the problems of women in the third world. Taking as her point of departure the predicament of poor women in India, she shows how philosophy should undergird basic constitutional principles that should be respected and implemented by all governments, and used as a comparative measure of quality of life across nations.